Moluccan moods international (1990)
Programma: 6 october Siri Mau, Formecis, Sagita, Galaxy Band, Lawa Mena Band, Tifa Collectief, Penyanisuling, Bahana, Tanase, Gong Gong, Tino Tamba, Fuzue & Senemali.